A review on microRNA detection and expression studies in dogs - Varvil, Mara S.; dos Santos, Andrea Pires (Frontiers in Veterinary Science, 2023)
MicroRNAs (miRNAs) are small non-coding RNAs that function by post-transcriptional regulation of gene expression. Their stability and abundance in tissue and body fluids makes them promising potential tools for both the diagnosis and prognosis of diseases and attractive therapeutic targets in humans and dogs. Studies of miRNA expression in normal and disease processes in dogs are scarce compared to studies published on miRNA expression in human disease. In this literature review, we identified 461 peer-reviewed papers from database searches using the terms "canine", "dog", "miRNA", and "microRNA"; we screened 244 for inclusion criteria and then included a total of 148 original research peer-reviewed publications relating to specific miRNA expression in canine samples. We found an overlap of miRNA expression changes between the four groups evaluated (normal processes, non-infectious and non-inflammatory conditions, infectious and/or inflammatory conditions, and neoplasia) in 39 miRNAs, 83 miRNAs in three of the four groups, 110 miRNAs in two of the three groups, where 158 miRNAs have only been reported in one of the groups. Additionally, the mechanism of action of these overlapping miRNAs varies depending on the disease process, elucidating a need for characterization of the mechanism of action of each miRNA in each disease process being evaluated. Herein we also draw attention to the lack of standardization of miRNA evaluation, consistency within a single evaluation method, and the need for standardized methods for a direct comparison.